Promoting Child and Adolescent Health. Issue 6 (November 2020) - Callister, Lynn Clark
Abstract : Forty distinguished global health professionals authored a report on the work of the World Health Organization, the United Nations Children's Fund, and the Lancet Commission on child and adolescent health, suggesting that the health and future of children and adolescents should be the central focus of the Sustainable Development Goals. Our global health and nursing expert, Dr. Callister, covers the details of the report and how nurses can promote the health of children and families in the United States and globally.